Putting gender at the heart of climate security - Caroli, Giulia; Tavenner, Katie (CGIAR FOCUS Climate Security, 2022)
While over the past few years, the nexus between climate change and security has received considerable attention in both policy circles and academia, the gender dimensions and implications embedded in these issues remain largely unexplored. However, ignoring these dynamics threatens to disempower and exclude socially marginalized groups in policies and interventions, preventing development and peace outcomes from reaching their maximum potential. It is particularly important to understand how gender shapes people’s experiences of insecurity in the context of a changing climate and develop appropriate strategies to address the specific risks women and men face based on their intersecting social identifies.